(3GdehTM (B((3aj TQM GdcGajI(B)s - (3TeS GdOjf eMeO Hf CHj HcQ Hf eMQR Hf eMeO GdNHjUjs; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s ((3CMeO Hf YHOGddg Hf MSf Hf eMeO Hf YjSi Hf jMji GdMOGO s)
(3ChdgG (B:s
(3hCMeOg ceG jSJMb Cf jMeO GdcdeI Cj GdJj hVYJ aj GUWdGM GdfMGI s
(3BNQgG (B:s
(3haj GVQHf GVQHhG HGdhGh hGdeaJhM eG bHdgG djfbdH CdakG cbhdc aj GVQHf GVQHG JTHjgkG dgG HGdJfhjf Je GdcJGH s
(3eged GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs